Hubungan Lama Duduk Dengan Kejadian Nyeri Punggung Bawah Pada Mahasiswa Fakultas Kedokteran Unisba Tingkat 3 Tahun 2022 - Wizdan Nafi Alfiansyah; Cice Tresnasari; Susanti dharmmika (Bandung Conference Series: Medical Science, 2023)
Abstract. Globally, there were 568.4 million common cases of low back pain in 2019 and the incidence was higher in students at the Faculty of Medicine with relatively tight class hours. This study aims to determine the relationship between prolonged sitting and the incidence of low back pain in third year students of the Faculty of Medicine Unisba in 2022. This type of research is quantitative with an analytic observational method and a cross sectional approach design. The instrument used is a questionnaire. A sample of 134 third year students at the Faculty of Medicine, Unisba in 2022, used the total sampling technique. The data analysis used was univariate and chi square test for bivariate analysis. Most of third year students of the Faculty of Medicine Unisba in 2022 experience lower back pain. It was found that there was a significant relationship between sitting duration and complaints of low back pain in 3rd year Unisba Medical Faculty students in 2022 with p-value = 0.034 (p <0.05). Sitting for a long time causes an increase in muscle contractions which produce waste products in the form of lactic acid and then cause pain in the lower back. It was concluded that prolonged sitting was associated with lower back pain. Keywords: Prolonged Sitting, Medical Student, Low Back pain Abstrak. Secara global, terdapat 568,4 juta kasus umum nyeri punggung bawah pada tahun 2019 dan insidensi lebih tinggi pada mahasiswa Fakultas Kedokteran dengan jam kuliah yang terbilang padat. Penelitian ini bertujuan untuk mengetahui hubungan lama duduk dengan kejadian nyeri punggung bawah pada mahasiswa Fakultas Kedokteran Unisba tingkat 3tahun 2022. Jenis penelitian ini adalah kuantitatif dengan metode observasional analitik dan rancangan pendekatan cross sectional. Instrumen yang digunakan berupa kuesioner. Sampel sebanyak 134 mahasiswa tingkat 3 Fakultas Kedokteran Unisba tahun 2022 dengan teknik total sampling. Analisis data yang digunakan adalah univariat dan uji chi square untuk analisis bivariat. Sebagian besar mahasiswa Fakultas Kedokteran Unisba tingkat 3 tahun 2022 mengalami nyeri punggung bawah. Didapatkan bahwa terdapat hubungan bermakna antara lama duduk dengan keluhan nyeri punggung bawah pada mahasiswa Fakultas Kedokteran Unisba tingkat 3 tahun 2022 dengan p-value= 0.034 (p < 0,05). Hal tersebut karena duduk dalam waktu lama menyebabkan peningkatan kontraksi otot yang menghasilkan produk sisa berupa asam laktat dan kemudian mengakibatkan nyeri pada punggung bawah. Disimpulkan lama duduk berhubungan dengan nyeri punggung bawah. Kata Kunci: Duduk Lama, Mahasiswa Fakultas Kedokteran, Nyeri Punggung Bawah